Development Of Health Education Management Models In Elementary Schools - Salfiyadi, Teuku; Nuraskin, Cut Aja; Reca, Reca (Dinamika Governance : Jurnal Ilmu Administrasi Negara, 2022)
ABSTRACT This study aims to explain the development of the Health Education Management model, especially for elementary school students. The methodology used is Research and Development. This research was conducted at an elementary school in the city of Banda Aceh. Data was collected using questionnaires, in-depth interviews, and observations. Analysis and testing of data using t-test. The results showed that there were significant differences in students' understanding before and after the intervention. Implementation of effective and efficient health education management in primary schools in Banda Aceh City. These results were proven by statistical t-test at a significance level of 0.919, ie 0.000 < 0.005. Keywords: Management, education, health. ABSTRAK Penelitian ini bertujuan untuk menjelaskan perkembangan model Manajemen Pendidikan Kesehatan khususnya pada siswa sekolah dasar. Metodologi yang digunakan adalah Research and Development. Penelitian ini dilakukan di sebuah sekolah dasar di kota Banda Aceh. Pengumpulan data dilakukan dengan menggunakan kuesioner, wawancara mendalam, dan observasi. Analisis dan pengujian data menggunakan uji-t. Hasil penelitian menunjukkan bahwa terdapat perbedaan pemahaman siswa yang signifikan sebelum dan sesudah intervensi. Penerapan manajemen pendidikan kesehatan yang efektif dan efisien di sekolah dasar di Kota Banda Aceh. Hasil tersebut dibuktikan dengan uji-t statistik pada taraf signifikansi 0,919, yaitu 0,000 < 0,005. Kata kunci: Manajemen, pendidikan, kesehatan.